Ursula. - Kennedy, Randy; Simpson, Lorna; Sante, Luc; Sherald, Amy; Bennett, Alissa; Coste Lewis, Robin; De Monchaux, Thomas (Hauser & Wirth : New York, 2018)
Goode Bryant, Linda ; Appelbroog, Ida ; Sante, Luc ; Phifer, Thomas ; Sherald, Amy ; Matsutani, Takesada ; Horn, Roni ; Woodman, Betty ; Whitten, Jack
boek
Keywords: Hauser, Ursula